Interaksi faktor personal, perilaku, dan lingkungan dalam motivasi belajar ipas: studi kualitatif di kelas iv sekolah dasar - Helmalia Niken Alfi; Idam Ragil Widianto Atmojo; Roy Ardiansyah (Universitas Sebelas Maret, 2026)
This study aims to analyze the interaction of personal, behavioral, and environmental factors in shaping students’ motivation to learn IPAS (Natural and Social Sciences) based on Albert Bandura’s social cognitive theory. The research employed a descriptive qualitative approach involving 33 fourth-grade students of SDN Sambi 3, Sragen, selected through purposive sampling as the first cohort experiencing the integration of science and social studies into IPAS within the Merdeka Curriculum. Data were collected through non-participatory observation, semi-structured interviews with the teacher and ten students, and a 44-item questionnaire developed from indicators of social cognitive theory. The findings indicate that self-efficacy fosters confidence, persistence, and readiness to face new tasks, although some students remain hesitant or easily discouraged. The physical classroom environment generally supports the learning process, despite challenges such as noise and limited comfort. Social relationships with teachers and peers enhance motivation through collaboration, guidance, and positive reinforcement. Teachers and peers also serve as role models, providing discipline and enthusiasm that inspire students. Overall, this study emphasizes the presence of reciprocal determinism, namely the reciprocal interaction among personal, behavioral, and environmental factors that collectively shape students’ motivation to learn IPAS.